Drug-excipient compatibility testing of cilostazol using FTIR and DSC analysis - Diño, Syrine Faith; Edu, Alia Denise; Francisco, Ralph Gean; Gutierrez, Emmanuel; Crucis, Perlita; Lapuz, April Mergelle; Carandang, Rogie Royce; Miranda, Kevin Jace (2023)
Cilostazol possesses pharmacological restrictions, such as its absorption being limited by its dissolution rate, and formulation studies must be employed accordingly to generate an optimized formulation. A drug-excipient compatibility analysis is conducted to determine any interactions that may affect the formulation in order to guarantee the stability,bioavailability, and manufacturability of solid dosage forms. To identify any incompatibilities, cilostazol alone and in combination with the individual excipients such as microcrystalline cellulose, crospovidone, magnesium stearate, isopropyl alcohol, sodium lauryl sulfate, polyvinylpyrrolidone K30, and corn starch were subjected to Fourier-transform infrared spectroscopy (FTIR) equipped with an attenuated total reflectance method and heat-flow differential scanning calorimetry (DSC) with a temperature ranging from 30–400 °C at 10 °C/min ramp rate. The FTIR analysis of cilostazol alone and combined with excipients revealed no evidence of chemical or physical instability. Minor changes in the appearance of the absorbance bands in the FTIR comparison can be seen primarily due to the chemical characterization of the excipients, but the characteristic peaks of cilostazol were still present. As for DSC compatibility analysis, the % difference in cilostazol's principal peak temperature alone and with excipients showed no significant change. This implies that no incompatibilities exist between cilostazol and the excipients.
Keywords: Drug efficacy; Spectrum analysis